PERILAKU PEMILIH PEMULA DALAM PILKADA SERENTAK DI Kecamatan Ciomas Kabupaten Serang TAHUN 2015 - Basuki Rahmat; Esther Esther (Jurnal Ilmu Pemerintahan Widya Praja, 2016)
Act No. 10 of 2008 on general elections to mention that voters are those who are first time to vote and aged 17 years or older or are/have been married have the right to vote in elections (and election).Voters beginners who are just entering the age of suffrage also do not yet have broad political range, todetermine where they should vote. So, sometimes what they choose is not as expected.The reason this is causing voters are very prone to be influenced and approached the materialapproach to the political interests of parties politik. Ketidaktahuan in terms of practical politics,especially with the choices in elections or local elections, voters often do not make rational thought andmore thoughtterm interests short.New voters are often only used by political parties and politicians to serve political interests, forexample be used for fundraising period and the formation of the party underbow organization.